2018
DOI: 10.1371/journal.pone.0204079
|View full text |Cite
|
Sign up to set email alerts
|

Dental anomalies and lesions in Eastern Atlantic harbor seals, Phoca vitulina vitulina (Carnivora, Phocidae), from the German North Sea

Abstract: Skulls of 1,901 Eastern Atlantic harbor seals (Phoca vitulina vitulina) were systematically studied for externally visible dental anomalies and lesions. The sample comprised 927 males and 974 female individuals, with age at death ranging between 1 week and 25 years. Most of the skulls originated from animals collected in 1988, when the population suffered from a mass mortality event caused by the phocine distemper virus (PDV). Mean age (± SD) of females (6.7 ± 6.4 years) was higher (p = 0.002) than that of mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 54 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…It has further been demonstrated that the analysis of skeletal material from museum collections is a means of retrospectively obtaining information on the health status of mammal populations and its changes over time. Previous studies on skeletal material from harbor seals inhabiting the German North Sea analyzed the prevalence and spectrum of dental anomalies and lesions [34] and of osteoarthritic changes of the temporomandibular joint [35]. By combining the results of the present and our previous studies with those of future studies addressing other issues, e.g.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…It has further been demonstrated that the analysis of skeletal material from museum collections is a means of retrospectively obtaining information on the health status of mammal populations and its changes over time. Previous studies on skeletal material from harbor seals inhabiting the German North Sea analyzed the prevalence and spectrum of dental anomalies and lesions [34] and of osteoarthritic changes of the temporomandibular joint [35]. By combining the results of the present and our previous studies with those of future studies addressing other issues, e.g.…”
Section: Discussionmentioning
confidence: 74%
“…The studied specimens (S1 Table) are permanently deposited in the collection of the Zoological Institute of the University of Kiel (ZIK), Germany, and accessible upon request. Previous studies by our group on the harbor seal skull material from this collection addressed the spectrum and prevalence of dental anomalies and lesions [34] and of osteoarthritic changes of the temporomandibular joint [35]. Age determination on the seals had been performed by Abt [36], based on cement-layer-analysis in canines or gross morphological criteria for individuals younger than one year.…”
Section: Methodsmentioning
confidence: 99%
“…The skulls originated from individuals that had been collected between 1958 and 1999 at different locations along the German North Sea coast. The analysed skulls are part of a larger collection that has previously been studied for dental anomalies and lesions (Kahle et al, 2018) and osteoarthritic lesions of the temporomandibular joint (Ludolphy et al, 2018). Only complete and undamaged skulls were included in the study.…”
Section: Methodsmentioning
confidence: 99%
“…The skulls originated from individuals that had been collected between 1958 and 1999 at different locations along the German North Sea coast. The analysed skulls are part of a larger collection that has previously been studied for dental anomalies and lesions (Kahle et al, 2018) Doutt (1942) and Sivertsen (1954). a Between the palatine processes of the maxillae.…”
Section: Study Samplementioning
confidence: 99%
“…1A ) is the result of a partial division of a single tooth bud ( Lucas & Schoch, 1987 ). It is the most commonly reported double tooth pathology with a wide representation across terrestrial and marine mammals, including extant representatives of Hominidae ( Agnihotri, Marwah & Goel, 2007 ; Camargo, Aritaa & Watanabe, 2016 ; Ertaş et al, 2014 ; Jain, Yeluri & Munshi, 2014 ; Knežević et al, 2002 ; Mahendra et al, 2014 ; Sharma et al, 2015 ; Shokri, Baharvand & Mortazavi, 2013 ; Tasa, 1998 ; Tsesis et al, 2003 ), Pinnipedia ( Abbott & Verstraete, 2005 ; Kahle et al, 2018 ), Felidae ( Aghashani et al, 2016 ; Gomerčić et al, 2009 ; Mestrinho et al, 2018 ), Ursidae ( Clark et al, 2017 ), Cercopithecidae ( Colyer, 1928 ), Equidae ( Easley, 2006 ), Talpidae ( Feldhamer & Towery, 2010 ; Kawada et al, 2006 ; Kawada et al, 2011 ), Canidae ( Gisburne & Feldhamer, 2005 ; Hitchin & Morris, 1966 ), Mustelidae ( Hauer, 2002 ), Cetacea ( Loch et al, 2011 ; Norton, 2009 ), and Muridae ( Sofaer, 1969 ). Gemination is also reported in the extinct taxa Coryphodontidae ( Lucas & Schoch, 1987 ), Condylarthra ( Rose & Smith, 1979 ), and Mammuthus ( Burns, Baker & Mol, 2003 ).…”
Section: Introductionmentioning
confidence: 99%